Condensed matter physics - Marder, Michael P., 1960- (Hoboken, N.J. : John Wiley & Sons, 2010)
'This second edition presents an updated review of the whole field of condensed matter physics. It consolidates new and classic topics from disparate sources, teaching not only about the effective masses of electrons in semiconductor crystals and band theory, but also about quasicrystals, dynamics of phase separation, why rubber is more floppy than steel, granular materials, quantum dots, Berry phases, the quantum hall effect, and Luttinger liquids'--
Includes bibliographical references and index.
Keywords: Condensed matter; Solid state physics